DRAMATURGY OF GENDER ROLES IN PERSONAL OUTREACH ON SOCIAL MEDIA THROUGH RELIGIOUS TEXTS - Saidah, Musfiah; Maulidia, Maya; Ningrum, Diah Ayu Kusuma; Sahfi, Rafiq Subhi (Center for Gender and Child Studies (Pusat Studi Gender dan Anak) LP2M UIN Syarif Hidayatullah Jakarta, 2023)
Abstract. Social media, as a platform that allows individuals to share personal stories with a wide audience, has become an important vehicle for personal stories. Religious texts, on the other hand, are often used as a tool to articulate individual feelings and experiences, as well as provide moral and spiritual guidance. This study aims to explain how gender role dramaturgy occurs in personal accounts on social media through religious texts. Is there a difference in influence between men and women in sharing Islamic words through social media and how does dramaturgy theory answer this. This research is a type of field research. Data collection was carried out by interviewing, observing, and tracing written sources such as journals and articles related to the object of research. Meanwhile, data analysis was carried out using qualitative data analysis techniques. The results of this study found several points. First, what is the theory of dramaturgy. Second, the difference between men and women. Third, social media is a medium of da'wah. This research reveals that gender dramaturgy influences the way individuals compose and present their personal stories through religious texts on social media. This underscores the importance of understanding gender roles and social norms in social media content analysis, and the implications for how we understand individual identities and experiences in today's digital context. Abstrak. Media sosial, sebagai platform yang memungkinkan individu untuk berbagi kisah pribadi dengan khalayak luas, telah menjadi kendaraan penting untuk cerita-cerita personal. Di sisi lain, teks keagamaan sering digunakan sebagai alat untuk menyatakan perasaan dan pengalaman individu, serta memberikan panduan moral dan spiritual. Penelitian ini bertujuan untuk menjelaskan bagaimana dramaturgi peran gender terjadi dalam akun personal di media sosial melalui teks keagamaan. Apakah ada perbedaan pengaruh antara pria dan wanita dalam berbagi kata-kata Islami melalui media sosial, dan bagaimana teori dramaturgi menjawab hal ini. Penelitian ini merupakan jenis penelitian lapangan. Pengumpulan data dilakukan dengan wawancara, observasi, dan penelusuran sumber tertulis seperti jurnal dan artikel terkait objek penelitian. Sementara itu, analisis data dilakukan dengan menggunakan teknik analisis data kualitatif. Hasil penelitian ini menemukan beberapa poin. Pertama, apa itu teori dramaturgi. Kedua, perbedaan antara pria dan wanita. Ketiga, media sosial sebagai medium dakwah. Penelitian ini mengungkapkan bahwa dramaturgi gender memengaruhi cara individu menyusun dan menyajikan cerita pribadi mereka melalui teks keagamaan di media sosial. Hal ini menegaskan pentingnya memahami peran gender dan norma-norma sosial dalam analisis konten media sosial, dan implikasinya terhadap pemahaman identitas dan pengalaman individu dalam konteks digital saat ini.